GAMBARAN PENGETAHUAN, SIKAP DAN TINDAKAN MASYARAKAT TENTANG PROTOKOLER KESEHATAN PADA MASA PANDEMI COVID-19 DI KELURAHAN GUNUNG SARIK WILAYAH KERJA PUSKESMAS BELIMBING - Eliwarti; Dozi Rianza; Ramadini, Indri (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Coronavirus Disease 2019 (Covid19) can cause respiratory tract infections in humans, ranging from the common cold to serious diseases such as MERS (Middle East Respiratory Syndrome) and SARS (Severe Acute Respiratory Syndrome). Transmission of Covid-19 can occur from person to person through respiratory droplets from coughs and sneezes. As of 15 April 2020, the prevalence of Covid-19 in Indonesia was quite high, with a total of 1,589,359 people with a death rate of 43,073 people. The acceleration of the spread rate can also be seen from the data on the highest incidence of Covid-19 cases in the province of West Sumatra, where the city of Padang is the area with the highest incidence of Covid-19, namely 17,037 positive confirmed cases as of April 23, 2021. Community knowledge and attitudes in dealing with the Covid-19 pandemic are very it is important to be able to reduce the risk of infection between fellow communities. The purpose of this study was to describe the knowledge, attitudes, and actions of the community regarding health protocols during the Covid-19 Pandemic. The research design used was descriptive, with a total sample of 89 respondents who were selected using a purposive sampling technique. Data collection using a questionnaire. The results of the univariate analysis showed that 42% of the community had good knowledge of health protocols, 60.7% had a negative attitude about health protocols and 67.4% of the community had unfavorable behavior regarding health protocols. Good knowledge from the community in dealing with the Covid-19 pandemic is expected to make the community take concrete actions to reduce the risk of contracting Covid-19.